DAMPAK PERGESERAN PARADIGMA PEMBELAJARAN TERHADAP PSIKOLOGIS GURU DAN SISWA MASA PANDEMI COVID-19 - Eka Putra Romadona; Syaiful Arif (IAIN Ponorogo, 2021)
Abstract: The educational process that was formerly carried out in a conventional or face-to-face way, during the pandemic the process has to be transferred online. Changes made in a short time and on a global scale without careful preparation can create deep feelings of rejection in the individual. The study was designed with a descriptive design of the phenomenon and was performed at the man 2 ponorogo to be precise in the xi class. 13 uambn and unbn teachers became informers in the study, along with 15 sophomores of both the science, ips, and religion were among the informants in the study. Studies show that performing online learning increases learners' stress. Online learning contributes significantly to the increased fear of teachers for the effectiveness of learning and the role conflict teachers should feel especially for teachers with school-age children. Key words: covid-19 pandemic, learning paradigm, psychological, paradigm